Activation of Sirtuin 3 by Silybin Attenuates Mitochondrial Dysfunction in Cisplatin-induced Acute Kidney Injury - Li, Yin; Ye, Zengchun; Lai, Weiyan; Rao, Jialing; Huang, Wanbing; Zhang, Xiaohao; Yao, Ziying; Lou, Tanqi (Frontiers in Pharmacology, 2017)
Silybin is a secondary metabolite isolated from the seeds of blessed milk thistle (Silybum marianum) that has anti-inflammatory, antioxidative, antifibrotic and antitumor properties. Here, we showed that silybin protected against cisplatin-induced acute kidney injury (AKI) by improving mitochondrial function through the regulation of sirtuin 3 (SIRT3) expression. Male SV129 and SIRT3 knockout (KO) mice were administered a single intraperitoneal (i.p.) injection of cisplatin with or without treatment with silybin. Moreover, cultured HK2 cells were used to evaluate mitochondrial morphology and function. Our data suggested that silybin enhanced SIRT3 expression after cisplatin administration both in vivo and in vitro. Silybin treatment improved mitochondrial function and bioenergetics in wild-type, but not SIRT3-defective, cells and mice. Moreover, we demonstrated that silybin markedly attenuated cisplatin-induced AKI and tubular cell apoptosis and improved cell regeneration in a SIRT3-dependent manner. Collectively, these results suggest that silybin is a pharmacological activator of SIRT3 capable of protecting against cisplatin-induced tubular cell apoptosis and AKI by improving mitochondrial function. Thus, silybin could serve as a potential clinical renoprotective adjuvant treatment in cisplatin chemotherapy.